The German-Central European supply chain revisited - Doris Hanzl-Weiss; Oliver Reiter (FIW - Research Centre International Economics, 2025)
In this policy brief, we look at the current situation in the automotive industry in Austria, Germany and the Visegrád countries, as they form a tightly integrated supply chain for the production of automobiles. Our analysis highlights the central role of Germany in this setting, as the main producer and exporter of cars. Due to this key position, the current negative economic developments in Germany mostly spill over into these countries. Currently, the industry faces many challenges. The imposition of a 15% tariff on cars and car parts by the US will decrease EU exports, further aggravating the difficult situation in its automotive industry. Our recommendation is to see the green and digital transitions as an opportunity to expand the capabilities of European car producers, to view competition from China as a chance, and to keep regulatory certainty to steer the necessary change.
Keywords: 330